PENINGKATAN MINAT BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCHDI KELAS IV SDN 06 LUBUK JANTAN - Efrianti Efrianti (STKIP Pesisir Selatan, 2019)
The interest in learning is one of the important factors for students' success in learning. However, interest in learning fourth grade students of SDN 06 Lubuk Jantan in mathematics subjects was found to be still low. The purpose of this study was to describe and obtain information about increasing students' interest in learning in mathematics through the Index Card Type Active Learning Strategy Match in Class IV SDN 06 Lubuk Jantan. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 23 fourth grade students of SDN 06 Lubuk Jantan. The research data was collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Active Learning Strategy Type Index Card Match can increase students' interest in learning in mathematics subjects in Class IV SDN 06 Lubuk Jantan. The interest in student learning in the first cycle was 69.67 increasing to 84.36.